2012
DOI: 10.1136/bcr-2012-007056
|View full text |Cite
|
Sign up to set email alerts
|

Closed trauma,Mycoplasma hominisosteomyelitis, and the elusive diagnosis of Good's syndrome

Abstract: Mycoplasma hominisseptic arthritis has a well-established association with hypogammaglobulinaemia, but is rarely seen in immunocompetent hosts. An association also exists with a closed trauma and a predisposition toM hominisbone infections. In this clinical case report, a patient withM hominisosteomyelitis following a closed trauma was diagnosed using 16S ribosomal studies, and led to the diagnosis of a severe underlying immunodeficiency syndrome known as Good's syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…M. hominis can cause a variety of genital infections, including bacterial vaginosis [26], nongonococcal urethritis, pelvic inflammatory disease, and prostatitis [23]. In recent years, extragenital M. hominis infections have been reported [11,22,29]. M. hominis BSI is one of the serious invasive infections caused by this pathogen, and treatment is almost certainly required [18].…”
Section: Introductionmentioning
confidence: 99%
“…M. hominis can cause a variety of genital infections, including bacterial vaginosis [26], nongonococcal urethritis, pelvic inflammatory disease, and prostatitis [23]. In recent years, extragenital M. hominis infections have been reported [11,22,29]. M. hominis BSI is one of the serious invasive infections caused by this pathogen, and treatment is almost certainly required [18].…”
Section: Introductionmentioning
confidence: 99%
“…The recent cases describe isolation of M. hominis a number of days following hospital admission with patients having contributing factors such as head trauma, neurosurgery, genitourinary or delivery manipulations 1–16. A separate group at increased risk of extra-genital M. hominis infections are those with congenital and acquired immunodeficiency due to impaired cell-mediated and antibody-mediated immunity; these include immune-suppressive therapy post organ transplantation, collagen vascular disease and hypogammaglobulinaemia,16 18 19…”
Section: Discussionmentioning
confidence: 99%
“…Extra genital sites of infection include vascular site infections, surgical wounds, joint infection and respiratory tract infections,16 18 19 As described, M. hominis has also emerged as an infrequent but important cause of postoperative central nervous system infections. M. hominis asymptomatically colonises the urogenital tract (15%) and more rarely the respiratory tract mucosa of healthy individuals 1–16.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mycoplasma hominis is an opportunistic human pathogen and resides as a commensal on the mucosal surfaces of the cervix or vagina of 21% to 53% of sexually mature, asymptomatic women; this is somewhat lower in the urethra of males [3]. However, M. hominis has also been associated with clinically diverse diseases including; urogenital diseases [4] [5], postpartum fever [6], pneumonia [7], meningitis [8] [9] and septic arthritis [10] [11]. Although this organism has only been isolated from humans, it was found that in utero administration of M. hominis to pregnant macaque monkeys led to preterm labour and foetal lung injury [12].…”
Section: Introductionmentioning
confidence: 99%